Implementation of the Simple Multi-Attribute Rating Technique for Determining Home Ownership Loan Housing - Wahidin, Ahmad Jurnaidi; Nabila Sari, Marhani (International Journal of Mechanical Computational and Manufacturing Research, 2024)
This study applied the Simple Multi-Attribute Rating Technique (SMART) to determine the best housing option based on Home Ownership Loans. Five criteria were identified as crucial for Home Ownership Loans housing evaluation: price, location, facilities, land area, and building area. Each criterion was assigned a weight reflecting its relative importance in the decision-making process. Four housing alternatives were evaluated using a rating scale to measure how well each met the criteria. The evaluation showed that Magnolia Residence was the top-ranked housing option with a total score of 0.73, followed by Puri Jaya, Widari Village, and CitraRaya Tangerang. The SMART method proved effective in assisting prospective buyers in making informed and objective decisions when selecting Home Ownership Loans housing. Future research is recommended to include additional criteria, expand housing alternatives, involve more respondents, and develop web-based or mobile applications to facilitate the use of the SMART method